TAVI for patients with normal-flow low-gradient compared to high-gradient aortic stenosis - Steffen, Julius; Andreae, David; Nabauer, Michael; Reißig, Nikolas; Doldi, Philipp M.; Haum, Magda; Orban, Martin; Theiss, Hans; Rizas, Konstantinos; Braun, Daniel; Peterß, Sven; Hausleiter, Jörg; et al. (International journal of cardiology, 2023)
Normal-flow (stroke volume index, SVi >35 ml/m2) low-gradient (dPmean <40 mmHg) aortic stenosis (NFLG-AS) is subject of scientific debate. Guidelines fail to give conclusive treatment recommendations. We hypothesized that NFLG patients are heterogenous, containing a subgroup similar to high-gradient aortic stenosis patients (dPmean ≥40 mmHg, HG-AS) concerning characteristics and outcomes. 2326 patients undergoing transcatheter aortic valve replacement (TAVI) at our centre between 2013 and 2019 were analysed. 386 patients fulfilled criteria of NFLG-AS. Their median dPmean was 33 mmHg, which was used for grouping (204 patients with higher gradient NFLG-AS, 186 patients with lower gradient NFLG-AS). They were compared to 956 HG-AS patients. Characteristics of lower gradient NFLG-AS patients differed from HG-AS patients in many aspects while higher gradient NFLG-AS and HG-AS patients were mostly similar, underscored by higher Society of Thoracic Surgeons scores in lower gradient NFLG-AS (lower gradient NFLG-AS, 3.9, HG-AS, 3.0, p = 0.03, higher gradient NFLG-AS, 3.0, p = 0.04). Procedural complications were comparable. Estimated 3-year all-cause mortality was higher in lower gradient NFLG-AS compared to HG-AS patients (hazard ratio 1.7, p < 0.01), whereas mortality of higher gradient NFLG-AS was similar to HG-AS patients (hazard ratio 1.2, p = 0.31). Cardiovascular mortality was highest among lower gradient NFLG-AS patients (21.6% vs. higher gradient NFLG-AS, 15.4%, vs. HG-AS, 11.1%, p < 0.01). NFLG-AS patients are indeed heterogenous. NFLG-AS patients with higher gradients resemble HG-AS patients in clinical characteristics and outcomes and should not be treated differently. Lower gradient NFLG-AS patients have increased long-term mortality and the use of TAVI requires careful consideration. •Normal-flow low-gradient aortic stenosis (NFLG-AS) is a common subset.•Guidelines give no conclusive recommendations for patients with NFLG-AS.•Patients with NFLG-AS are a heterogeneous cohort; dPmean can discriminate subsets.•NFLG-AS patients with higher dPmean resemble high-gradient AS patients.•NFLG-AS patients with lower dPmean have an increased mortality after TAVI.